1978
DOI: 10.1111/j.1365-2672.1978.tb00779.x
|View full text |Cite
|
Sign up to set email alerts
|

The Development of the Anaerobic Spoilage Flora of Meat Stored at Chill Temperatures

Abstract: In meat juice medium under anaerobic conditions, spoilage bacteria utilized the following substrates: Microbacterium thermosphactum, glucose; Enterobacter, glucose and glucose‐6‐phosphate; Lactobacillus, glucose and arginine. On meat stored anaerobically. Lactobacillus grew faster than the other species at all temperatures between 2° and 15 °C. Enterobacter had a greater affinity for glucose than M. thermosphactum. As a result, high numbers of Enterobacter inhibited growth of M. thermosphactum under the glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
25
0
2

Year Published

1986
1986
2004
2004

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(30 citation statements)
references
References 9 publications
3
25
0
2
Order By: Relevance
“…In agreement with other studies, we found that the microbiota in vacuum-packed meat was dominated by LAB (6,40,50,53,57), with Enterobacteriaceae accounting for 1 to 10% of the microbiota. The level of Enterobacteriaceae and the level of AHL-producing bacteria as estimated by replica plating onto an AHL monitor strain were similar.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In agreement with other studies, we found that the microbiota in vacuum-packed meat was dominated by LAB (6,40,50,53,57), with Enterobacteriaceae accounting for 1 to 10% of the microbiota. The level of Enterobacteriaceae and the level of AHL-producing bacteria as estimated by replica plating onto an AHL monitor strain were similar.…”
Section: Discussionsupporting
confidence: 81%
“…At the time of rejection the typical off odor is putrid and slime is visible at the surface (15). The shelf life of vacuum-packed fresh meat products stored at chill temperatures is extended to weeks or months and the microbiota typically consists of lactic acid bacteria (LAB) and Enterobacteriaceae at levels of 10 8 and 10 6 CFU/g, respectively (6,40,50,53,57). Spoilage off-odors are characterized as dense, sour, and slightly putrid (8).…”
mentioning
confidence: 99%
“…Unlike the general aminopeptidases previously identified in dairy lactic acid bacteria, the only aminopeptidase purified from L. sakei so far does not hydrolyze N-terminal arginine (22). However, arginine is an essential amino acid for L. sakei and specifically promotes its growth in meat (19,21). The concentration of free arginine in raw meat is low, although it is relatively abundant in muscle myofibrillar proteins.…”
mentioning
confidence: 94%
“…In contrast, the ratios of hydrolysis rates obtained with Arg-derived substrates to those obtained with Lys-derived substrates were much lower for mammalian enzymes, e.g., 2.5 and 2.0 for rat liver and porcine liver enzymes, respectively (13). Among dipeptides, the maximal hydrolysis rate was detected against Arg-Arg, which also indicated that the catalytic activity is highly specific in order to release free arginine in L. sakei, which could promote the growth of this organism in meat (19,21). The kinetics of the hydrolysis of both Arg-AMC and Lys-AMC also indicated that the L. sakei Overall, a novel arginine aminopeptidase has been described with particular biochemical properties such as its acidic optimum pH and the activating effect of sodium chloride, which may be of the utmost importance for physiological and technological roles in the meat preservation and fermentation processes.…”
mentioning
confidence: 99%
“…Members of the family Enterobacteriaceae may also constitute part of the psychrotrophic microflora of vacuum-packaged meats [67,68,69,105,144]. Many Enterobacteriaceae, such as Citrobacter freundii, E. coli, Klebsiella pneumoniae and Salmonella spp., which are commonly found on meats do not grow because the temperature of the chilled storage is below their minimum growth temperatures of 5 to 7°C.…”
Section: Sake L Viridescens and The New Species C Piscicoia (L Camentioning
confidence: 99%